2000
DOI: 10.1094/mpmi.2000.13.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Pathogen-Induced Gene Can Be Mimicked by Auxin Insensitivity

Abstract: Following perception of a pathogenic attack, plants are able to develop a strong response with the corresponding activation of a plethora of defense-related genes. In this study we have characterized the mode of expression of the CEVI-1 gene from tomato plants, which encodes an anionic peroxidase. CEVI-1 expression is induced during the course of compatible viral and subviral infections, like many other defense-related genes, but is induced neither in incompatible interactions nor by signal molecules such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
4
40
0
1
Order By: Relevance
“…Auxin homeostasis is one of the components participating in the regulation of the defence response (Mayda et al 2000). So, deregulation of auxin efflux carrier in this study suppresses the defence response pathways.…”
Section: Discussionmentioning
confidence: 71%
“…Auxin homeostasis is one of the components participating in the regulation of the defence response (Mayda et al 2000). So, deregulation of auxin efflux carrier in this study suppresses the defence response pathways.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, CEVI-1 showed rapid activation if leaf segments were detached from the plant. However, the expression of CEVI-1 , either during disease or on detachment, was controlled by way of an SA-independent pathway, and neither ethylene nor jasmonic acid and wounding were able to induce expression of CEVI-1 in the plant (Mayda et al, 2000). These findings suggested that the expression of CEVI-1 could be controlled by a novel signaling pathway activated during disease in susceptible tomato plants.…”
Section: Introductionmentioning
confidence: 88%
“…These findings suggested that the expression of CEVI-1 could be controlled by a novel signaling pathway activated during disease in susceptible tomato plants. Additionally, the observation that the constitutive expression of CEVI-1 :: GUS in the Arabidopsis dth mutants concurs with an auxin-resistant phenotype in the plant prompted us to suggest that the mechanism upregulating the expression of CEVI-1 is related to an induced insensitivity to auxin that might be primed during disease (Mayda et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…syringae). En cuanto a su patrón de expresión, CEVI1 no es capaz de responder a tratamientos con las moléculas señalizadoras clásicas de defensa como el SA, ET o JA, ni a estímulos de herida (Mayda et al, 2000a). Todos estos datos sugieren que la expresión del gen CEVI1 parece responder a una nueva vía de señalización de defensa en plantas.…”
Section: Cevi1: Gen Inducible En Interacciones Víricas Compatiblesunclassified